МАТЕРИАЛЫ ПЕРВОГО КОНГРЕССА ОБЩЕСТВА СПЕЦИАЛИСТОВ ПО ОПУХОЛЯМ ГОЛОВЫ И ШЕИ МОСКВА, 18–19 ОКТЯБРЯ 2012 (Опухоли головы и шеи)
МАТЕРИАЛЫ ПЕРВОГО КОНГРЕССА ОБЩЕСТВА СПЕЦИАЛИСТОВ ПО ОПУХОЛЯМ ГОЛОВЫ И ШЕИ МОСКВА, 18–19 ОКТЯБРЯ 2012